Social security pension generosity and the effect on household saving - Elin Halvorsen; Zhiyang Jia; Herman Kruse; Trond C. Vigtel (Statistics Norway, Research Department, 2022)
This paper examines the substitution between pension wealth and household saving by studying Norway's 2011 pension reform. The analysis identifies the effect of reductions in social security pension generosity on household saving using cohort, time and sector variation in pension wealth induced by the reform. Our study focuses on saving behavior between ages 57-61 for the 1954- 1956 birth cohorts, who are the first three birth cohorts affected by a reduction in future pension wealth due to the reform. We find that they increased their saving rate around 1.2 percentage points (annually) after the reform, which corresponds to a five-year increase in household saving of about 27,000 NOK. When taking into account the remaining life-cycle changes to household saving, this corresponds to an offset effect of about 56 percent of the total loss in pension wealth.
Keywords: D14; E21; H55; 330; Pension reform; household saving; difference-in-difference; quasi-natural experiment